Historical dictionary of Nigeria - Falola, Toyin; Genova, Ann; Heaton, Matthew M. (Historical dictionaries of Africa., 2018)
"The Historical Dictionary of Nigeria: Second Edition introduces Nigeria's rich and complex history. Readers will find a wealth of information on pre-20th century history, Nigeria under British colonial rule, and important post-independence issues while providing greater attention to Nigeria's role in international relations, diaspora, and contributions to arts, film and culture in particular. This revised edition covers major developments since the last edition such as the rise of the terrorist group Boko Haram and the election of Muhammadu Buhari to the presidency in 2015 among others. This second edition of Historical Dictionary of Nigeria: Second Edition contains a chronology, an introduction, and an extensive bibliography. The dictionary section has over 1,000 cross-referenced entries on important personalities, politics, economy, foreign relations, religion, and culture. This book is an excellent resource for students, researchers, and anyone wanting to know more about Nigeria"--Publisher's description.